UPAYA MENINGKATKAN KREATIVITAS BELAJAR SISWA MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK - Fransiska Kusuma Ningrum; Giyono Giyono; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine the increasment of creative learning after attending group counseling services in students of class XII SMK SPP Lampung District academic year 2012/2013. The problem in this study was the low student’s creativity. Its sentence in this study was "was student creativity improve after attending group counseling services in students of class XII SMK SPP Lampung District academic year 2012/2013?". The method was quasi experimental with Time Series design. Subjects were six students recommended by teachers and school counselor. Data collection techniques used observation. The results obtained indicated that there was an increasment in student’s creativity learning after attending group counseling services, as shown from the results of the data analysis using Wilcoxon test, the results of pretest and posttest obtained zscore = -2.226 z table = 0 then, Ho is rejected and Ha accepted, which means there is an increasment student’s creativity in learning after attending group counseling services. The conclusion was an increasment student’s creativity in learning after participating in group counseling services in there is students of class XII SMK SPP Lampung District academic year 2012/2013. The advice given were (1) Students should be able to take part in group counseling services, to enhance the creativity of learning. (2) School counselor should conduct group counseling to help students improve learning creativity. (3) Other researchers should be able to do research on the same problem but try to use other approaches and techniques such as using positive reinforcement techniques.Keywords: Learning Creativity, Group Counseling, Guidance and Counseling